Microbiological, Biochemical, and Functional Aspects of Fermented Vegetable and Fruit Beverages - Lamia Ayed; Sana M’hir; Moktar Hamdi (Journal of Chemistry)
In recent years, the request for the functional beverages that promote health and wellness has increased. In fact, fermented juices are an excellent delivering means for bioactive components. Their production is of crucial importance to supply probiotics, in particular, for people with particulars needs like dairy-product allergic consumers and vegetarians. This review focuses on recent findings regarding the microbial composition and the health benefits of fermented fruit and vegetable beverages by lactic acid bacteria, kefir grains, and SCOBY as well as discussing the metabolites resulting from these fermentations process. Moreover, limits that could restrain their production at the industrial level and solutions that have been proposed to overcome these constraints are also reviewed.